2017
DOI: 10.1002/stem.2613
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Promotes Central Nervous System-Dependent Release of Mesenchymal Stem Cells

Abstract: Electro-acupuncture (EA) performed in rats and humans using front-limb acupuncture sites, LI-4 and LI-11, and Du-14 and Du-20 increased functional connectivity between the anterior hypothalamus and the amygdala and mobilized mesenchymal stem cells (MSC) into the systemic circulation. In human subjects, the source of the MSC was found to be primarily adipose tissue whereas in rodents the tissue sources were considered more heterogeneous. Pharmacological disinhibition of rat hypothalamus enhanced sympathetic ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 52 publications
1
38
0
2
Order By: Relevance
“…Electroacupuncture promotes the migration of BMCs by speeding up the process of synthesis and secretion of various endogenous factors . SDF‐1/CXCR4 axis is an essential signal participating to promote migration of the stem cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electroacupuncture promotes the migration of BMCs by speeding up the process of synthesis and secretion of various endogenous factors . SDF‐1/CXCR4 axis is an essential signal participating to promote migration of the stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Electroacupuncture promotes the migration of BMCs by speeding up the process of synthesis and secretion of various endogenous factors. 23 SDF-1/CXCR4 axis is an essential signal participating to promote migration of the stem cells. A study has shown that binding SDF-1 to its receptor, CXCR4, played a crucial role in the mobilization and migration of the bone marrow mesenchymal stem cells into the injured skin.…”
Section: Discussionmentioning
confidence: 99%
“…Both human and animal experiments have confirmed that electroacupuncture therapy has a definite effect on the treatment of pain, movement disturbance, tissue regeneration, and so on [ 39 44 ]. Some studies have found that the effects of acupuncture were mediated by the central nervous system, thus causing specific physiological effect that achieved the purpose of treatment and improved the growth of neurons, axonal regeneration, synaptic reconstruction, and the functional connection of target organs [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“… 68 In rats, electroacupuncture has also been shown to stimulate the release of mesenchymal stem cells that act to promote tissue repair, increase levels of anti-inflammatory cytokines, and enhance analgesia. 69 …”
Section: Acupuncture In Laboratory Animalsmentioning
confidence: 99%